Caracterização de rizobactérias associadas à Solanum lycocarpum St. Hil. quanto ao potencial biotecnológico para promoção de crescimento vegetal, enzimas e agentes antimicrobianos - Lisboa, Paulo Henrique Gomes (2020)
Solanum lycocarpum St. Hil., endemic plant of the Brazilian tropical savanna, known as the “Cerrado”, has been studied for its medicinal properties and for having the ability to grow in acidic and nutrient-poor lands, attracting interest in the investigation of its rhizospheric microbiota, which includes plant growth-promoting rhizobacteria (PGPR). Industrial enzymes and antibiotics can also be obtained from them. In this work, the biological nitrogen fixation capacity was tested in NFb semi-solid culture medium and 32.6% of the isolates showing positive results. In the inorganic phosphate solubilization tests, 45.8% of the isolates demonstrated this capacity in nutrient agar supplemented with insoluble phosphate. The solubilization index (SI) for calcium phosphate by the bacterial isolates grown in solid medium varied from 0 to 4.833. All bacteria produced indole acetic acid (ranging from 0.07 μg.mL-1 to 134.1 μg.mL-1) in Tryptic Soy Broth (TSB) 10% + L-tryptophan medium. In assays against pathogens, antagonistic activity was demonstrated against a spectrum of fourteen phytopathogenic fungi through the technique of direct pairing in Potato Dextrose Agar (PDA) medium and three clinical pathogens using the agar block method. The bacterial isolates were striated in special mediums whose carbon sources were substrates of the enzymes in the enzyme activity assays and 88.4% of them had at least one of these activities. The best isolates were identified by partial sequencing of the 16S gene as belonging to the genera Bacillus, Burkholderia and Microbacterium.